Answer:
1/6
Step-by-step explanation:
-3/4 - (-1/2) = - 1/4
-2/3 - 5/6 = - 3/2
-1/4 ÷ -3/2
Answer:
The first is 0.046 and the second is 0.033
Step-by-step explanation:
Applying the linear pair theorem, the measure of angle TSV in the image given is: 86°.
<h3>How to Apply the Linear Pair Theorem?</h3>
Given the following angles in the image above:
Measure angle RSU = (17x - 3)°,
Measure angle UST = (6x – 1)°
To find the measure of angle TSV, we need to find the value of x in the given expressions as shown below:
m∠RSU + m∠UST = 180 degrees (linear pair]
Substitute the values
17x - 3 + 6x - 1 = 180
Solve for x
23x - 4 = 180
23x = 180 + 4
23x = 184
x = 8
m∠TSV = 180 - 2(m∠UST) [Linear Pair Theorem]
m∠TSV = 180 - 2(6x - 1)
Plug in the value of x
m∠TSV = 180 - 2(6(8) - 1)
m∠TSV = 86°
Therefore, applying the linear pair theorem, the measure of angle TSV in the image given is: 86°.
Learn more about the linear pair theorem on:
brainly.com/question/5598970
#SPJ1
Answer: -15yx^2
Step-by-step explanation:
-12x^2 * y -3x^2 * y=
-12(x^2 * y)-3(x^2 * y)=
(-12-3)(x^2 * y)=
-15x^2 * y=-15yx^2